ANALISIS FAKTOR-FAKTOR PENYEBAB PEKERJAAN ULANG (REWORK) PADA PROYEK KONSTRUKSI BANGUNAN GEDUNG DI KOTA KUPANG - Gregorius Pius Usboko; Sebastianus Baki Henong (JURNAL TEKNIK SIPIL CENDEKIA (JTSC), 2022)
Implementation of a building construction project carried out through a certain management system. The project has a predetermined schedule and implementation plan. Common things that will occur if they are not in accordance with the schedule and implementation plan are delays in project implementation time and implementation costs. One of the factors causing the delay is due to rework activities on one or several items of construction work. The purpose of this study was to identify and analyze the factors that cause rework on building construction projects in the city of Kupang, East Nusa Tenggara Province. This study used a questionnaire instrument involving as many as 27 contractors, consisting of 12 site managers, 12 field implementers and 3 foreman. This research was conducted to see the dominant factor of rework in building construction projects in Kupang city. The results showed that the factors causing rework are known from managerial, design and resource factors which are the main causes of the emergence of rework in work. Operators working not according to procedures are one of the main causes of rework from the resource factor. Lack of teamwork is the cause of the rework of managerial factors. Unclear design or documentation is the cause of rework of design factors.